Three new species of Diaporthe from China based on morphological characters and DNA sequence data analyses - Zhou, Hao; Hou, Cheng-Lin (Phytotaxa, 2019)
In the present study, nine endophytic strains of Diaporthe from China were identified based on analyses of morphological characters and combined sequences of rDNA ITS, partial sequences from the translation elongation factor 1-α (tef1), β tubulin (tub2), histone H3 (his3), and calmodulin (cal) genes. Three new Diaporthe species, Diaporthe anhuiensis, Diaporthe huangshanensis and Diaporthe shennongjiaensis, are introduced in this paper with full descriptions and comparison with similar taxa. And two other known species, Diaporthe citrichinensis and Diaporthe eres are also described.